2020
DOI: 10.1016/j.jcbs.2020.09.007
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation of the effect of acceptance and commitment therapy on neural activation in clinical perfectionism

Abstract: Clinical perfectionism is associated with various cognitive processes including performance monitoring and emotion regulation. This exploratory study analyzed neurological data from a randomized controlled trial for clinical perfectionism that compared acceptance and commitment therapy (ACT) to a waitlist control. The objective was to assess the effect of ACT on neural activation. Twenty-nine participants underwent a functional near-infrared spectroscopy assessment during which they completed behavioral tasks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Data were recorded at 695 and 830 nm. After the experiment, spatial coordinates were obtained for each participant using the Polhemus PATRIOT digitizing software following procedures consistent with previous studies (Wan et al, 2018 ; Ong et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were recorded at 695 and 830 nm. After the experiment, spatial coordinates were obtained for each participant using the Polhemus PATRIOT digitizing software following procedures consistent with previous studies (Wan et al, 2018 ; Ong et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…NIRS-SPM was used to register the spatial coordinates of the channels to obtain Brodmann areas that provided the percentage of channel overlapping within a brain region. All channels with 50% or greater overlapping area within a region were averaged together to select channels for each ROI (Rorden and Brett, 2000 ; Wan et al, 2018 ), as delineated in Table 1 , followed by taking the square root of the signal power of the entire channel to normalize the signal (Ong et al, 2020 ). Finally, area under the curve (AUC) was computed by using the standard trapezoid function in Matlab (Wan et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, the effects of the neuropsychological educational approach to cognitive remediation were assessed by pre-and post-comparison of the oxyHb changes during 2-back tasks (Pu et al, 2014). Similarly, the effects of haptic-assisted meditation were evaluated using the attention network and sustained attention to response tasks (Zheng et al, 2019); further, the effects of acceptance and commitment therapy were assessed using behavioral tasks including editing, mirror image tracking, and circle tracking (Ong et al, 2020).…”
Section: Methodology For Evaluation Of Psychotherapeutic Effects Using Nirsmentioning
confidence: 99%
“…It has been suggested that this is because these individuals must exert significant effort to inhibit excessive emotion. In such cases, deactivation of the LPFC region is an index for improvement (Ohtani et al, 2009;Okamoto et al, 2010;Amano and Toichi, 2016;Glassman et al, 2016;Ong et al, 2020;Rosenbaum et al, 2020a,b; Table 2). Implementation of exposure therapy reduced the LPFC activity while watching videos of spiders in patients with arachnophobia (Rosenbaum et al, 2020b; Tables 1, 2).…”
Section: Nirs Index For Evaluation Of Psychotherapeutic Effectsmentioning
confidence: 99%